Study of 138 Neisseria meningitidis strains isolated from blood or cerebrospinal fluid in Lombardy between 2007 and 2010 - Laura Daprai; Maria Laura Garlaschi; Giuseppina Scelza; Damiano Picicco; Maria Cristina Garlaschi; Riccardo Rubini; Gloria Defilippi; Anna Pavan; Maria Gramegna; Erminio Torresani (Microbiologia Medica, 2012)
Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae type b cause the majority of cases of bacterial septicaemia in children and young adults. Disease epidemiology is evolving rapidly due to the introduction of vaccines and changing in bacterial antibiotic-resistance patterns. (Asymptomatic nasopharyngeal colonization with Neisseria meningitides occurs in 5-10% of adult). The aim of this study was to calculate the frequency of each serogroup of this pathogens involved in invasive infection and to study susceptibility to antibiotics of these strains. Between March 2007 and June 2010 we received, from 43 hospitals of Lombardy, 138 strains of Neisseria meningitidis, from 138 patients aged (2-80yrs). The most frequent serogroup was B (58%), followed by serogroup C (34%), serogroup G (4%) and W 135 (2%). Serogroup A end X accounted for 1% of invasive infection, each. We observed a decrease in susceptibility towards penicillin in 38% of strains. In addition we studied, by REP- PCR, genotype of 9 strains selected on the basis of epidemiological data.Among these strains, 3 different clusters according to the 3 small epidemic outbreaks occurred between June and September 2009, were recognised. Seven of these strains, although belonged to the same serogroup, brought about two different clusters. The present findings demonstrated that phenotypic data are not sufficient to define epidemic clusters, therefore molecular genotyping is required.